Bacterial Pigment Prodigiosin as Multifaceted Compound for Medical and Industrial Application - Ivan Guryanov; Ekaterina Naumenko (Applied Microbiology)
Prodigiosin is a fascinating compound that has been gaining attention in the scientific community for its diverse range of potential applications. From its vibrant red color to its unique chemical properties, prodigiosin has captured the interest of researchers looking for innovative solutions in various fields. Prodigiosin, a red pigment produced by certain bacteria such as Serratia marcescens, has attracted interest from pharmaceutical researchers due to its promising potential in various therapeutic applications. A number of studies have demonstrated the potential of prodigiosin as an antimicrobial agent. With the rise of antibiotic resistance in the environment, prodigiosin is a promising solution to combat resistant strains and improve the effectiveness of existing antibiotic therapy. Moreover, different studies have shown that this natural pigment has anticancer properties by inhibiting the growth and proliferation of cancer cells. Prodigiosin exerts its anticancer effects by inducing apoptosis in cancer cells without causing significant damage to healthy cells. In this review, we will attempt to summarize the capabilities of prodigiosin and its prospects as a valuable tool in pharmaceutical research, and also review recent studies focusing on the various industries in which prodigiosin can be applied and the exciting possibilities it holds in the future.